PENGARUH MODEL PROBLEM BASED LEARNING (PBL) TERHADAP HASIL BELAJAR SISWA KELAS V PADA MATERI BANGUN RUANG - Atep Lesmana; Mubarok Somantri; Hany Handayani; Yeni Novianti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2022)
The purpose of this study is to know the influence of Problem Based Learning (PBL) towards students learning result of grade on geometry materials. This study uses quantitative approach with quasi exsperiment research and Nonequivalent Control Group design. The population in this study were all of the student in the grade of SDN 2 Nagritengah. The taking sample in this study uses Non Probability Sampling with Saturation Sampling Technique. The collecting data on this study uses observation and test in the form of essay questions. The hipotesis exsperiment uses formulation t-test that starts with analysys test are normality test and homogenety test. The result of the study has shown there is an influence use Problem Based Learning (PBL) towards students learning result of grade on geometry materials. It’s based on hipotesis calculation. The result from t-test has gotten P-Value (Sig. 2 tailed) 0,000 < 0,05. The average result score on posttest in experiment group got 65,20 it’s better then the average posttest score in control group got 50,53.